GROSS MORPHOMETRIC MEASUREMENTS OF UDDER IN TELLICHERRY GOATS - S. Senthilkumar; R. Gnanadevi; T.A. Kannan; Geetha Ramesh; C. Balan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The present study was conducted with the aim of establishing the basic data about gross morphometric measurements in lactating and non-lactating (n=15 each) adult Tellicherry she-goats. These goats had two mammary glands (right and left halves) divided by an inter mammary groove and each had a single teat. Udder circumference and inter teat distance differed between lactating and non-lactating animals. Udder length (UL) width of right (RUW) and left (L-UW) quarter, right and left teat length, teat diameter at base (TDB), teat diameter at tip (TDT), Teatto floor distance (TFD) and teat end floor distance (TEFD), right and left teat diameter at base (TDB), right and left teat diameter at tip (TDT) did not differ between lactating and non-lactating Tellicherry she-goats.